Developmental changes in isometric strength: Longitudinal study in adolescent soccer players - Duarte, J. P.; Valente-dos-Santos, J.; Coelho e Silva, M. J.; Malina, R. M.; Deprez, D.; Philippaerts, R.; Lenoir, M.; Vaeyens, R. (International Journal of Sports Medicine, 2018)
This study aimed to examine longitudinal changes in isometric strength of the knee extensors (ImKE) and knee flexors (ImKF) at 30° and 60°. The sample was composed of 67 players aged 11.0-13.9 years at baseline over five years. Stature, body mass, skinfolds, and isometric strength (ImKE30°, ImKF30°, ImKE60° and ImKF60°) were measured. Fat mass and fat-free mass (FFM) were derived from skinfolds. Skeletal age was obtained using TW2 RUS. Multilevel random effects regression analyses extracted developmental polynomial models. An annual increment on chronological age (CA) corresponded to 5.6 N (ImKE30°), 2.7 N (ImKF30°), 4.6 N (ImKE60°) and 1.5 N (ImKF60°). An increment of 1 kg in FFM predicted isometric strength as follows: 1.2 N (ImKE30°), 2.1 N (ImKF30°), 3.1 N (ImKE60°) and 2.0 N (ImKF60°). The following equations were obtained: ImKE30°=5.759×CA+1.163×FFM; ImKF30°=-19.369+2.691×CA+0.693×CA2+2.108×FFM; ImKE60°=4.553×CA+3.134×FFM; and, ImKF60°=-19.669+1.544×CA+2.033×FFM. Although skeletal maturity had a negligible effect on dependent variables, age and body size, based on FFM, were relevant longitudinal predictors. During adolescence, systematic assessment of knee extensors and knee flexors are strongly recommended to prevent impairment of knee muscle groups.